Exploring Defocus Matting: Non-Parametric Acceleration, Super-Resolution, and Off-Center Matting - Joshi, Neel; Matusik, Wojciech; Avidan , Shai; Pfister, Hanspeter; Freeman, William T. (IEEE Computer Graphics and Applications, 2007)
Defocus matting is a fully automatic and passive method for pulling mattes from video captured with coaxial cameras that have different depths of field and planes of focus. Nonparametric sampling can accelerate the video-matting process from minutes to seconds per frame. In addition, a super-resolution technique efficiently bridges the gap between mattes from high resolution video cameras and those from low-resolution cameras. Off-center matting pulls mattes for an external high-resolution camera that doesn’t share the same center of projection as the low resolution cameras used to capture the defocus matting data.